Modified single-incision MIS-TLIF with expandable tubular assistance for degenerative lumbar spine diseases - Hu, Wenlong; He, Fei; Sun, Kai; Wan, Haiwu; Ruan, Sijun; Huang, Bo (Frontiers in Surgery, 2025)
ObjectiveEvaluating the clinical value of the modified single-incision posterior median approach with expandable tubular assistance for lumbar interbody fusion in managing degenerative lumbar spine diseases.MethodA retrospective analysis was conducted on 121 patients with single-level degenerative lumbar spine disease treated in our spine surgery department from January 2017 to December 2021. Of these, 72 patients underwent a modified single-incision posterior median approach with expandable tubular assistance lumbar interbody fusion (single-incision MIS-TLIF group), while 49 patients received the classic open posterior median incision P-TLIF (open surgery group). We collected basic demographic data including age, gender, BMI, and surgical level. Surgical-related indicators such as operation time, intraoperative blood loss, postoperative drainage, length of hospital stay, hospital costs, and complication rates were compared between the two groups. Laboratory results [whole blood C-reactive protein (CRP), serum creatine kinase (CK)] and clinical outcomes [VAS scores for low back and leg pain, Oswestry Disability Index (ODI), excellent and good rate according to the modified MacNab criteria, and interbody fusion rate according to the Brantigan criteria] were also evaluated.ResultThere were no significant differences in the basic demographics between the two groups. The operation time, postoperative hospital stay, and hospital costs were also similar between the groups. However, significant differences were observed in intraoperative blood loss, postoperative drainage, and complication rates. On postoperative days 1 and 3, whole blood CRP and CK levels showed marked differences between the groups. At 3, 6, and 12 months postoperatively, the single-incision MIS-TLIF group had lower ODI scores and VAS scores for back pain compared to the open surgery group. The excellent and good rate according to the MacNab criteria was higher in the single-incision MIS-TLIF group. There were no significant differences in leg pain VAS scores and interbody fusion rates at 12 months postoperatively between the groups.ConclusionThe modified single-incision posterior median approach with expandable tubular assistance lumbar interbody fusion is highly effective in treating degenerative lumbar spine diseases. It results in less postoperative pain, faster recovery, and significant improvement in postoperative functional outcomes, making it a valuable treatment option.